Ceftriaxone increases glutamate uptake and reduces striatal tyrosine hydroxylase loss in 6-OHDA Parkinson’s model - Chotibut, Tanya (Mol Neurobiol, 2013)
Excess glutamatergic neurotransmission may contribute to excitotoxic loss of nigrostriatal neurons in Parkinson’s disease (PD). Here, we determined if increasing glutamate uptake could reduce the extent of tyrosine hydroxylase (TH) loss in PD progression. The beta-lactam antibiotic, ceftriaxone, increases the expression of glutamate transporter 1 (GLT-1), a glutamate transporter that plays a major role in glutamate clearance in central nervous system and may attenuate adverse behavioral or neurobiological function in other neurodegenerative disease models. In association with >80 % TH loss, we observed a significant decrease in glutamate uptake in the established 6-hydroxydopamine (6-OHDA) PD model. Ceftriaxone (200 mg/kg, i.p.) increased striatal glutamate uptake with ≥ 5 consecutive days of injection in nonlesioned rats and lasted out to 14 days postinjection, a time beyond that required for 6-OHDA to produce >70 % TH loss (~9 days). When ceftriaxone was given at the time of 6-OHDA, TH loss was ~57 % compared to ~85 % in temporally matched vehicle-injected controls and amphetamine-induced rotation was reduced about 2-fold. This attenuation of TH loss was associated with increased glutamate uptake, increased GLT-1 expression, and reduced Serine 19 TH phosphorylation, a calcium-dependent target specific for nigrostriatal neurons. These results reveal that glutamate uptake can be targeted in a PD model, decrease the rate of TH loss in a calcium-dependent manner, and attenuate locomotor behavior associated with 6-OHDA lesion. Given that detection of reliable PD markers will eventually be employed in susceptible populations, our results give credence to the possibility that increasing glutamate uptake may prolong the time period before locomotor impairment occurs.